2015
DOI: 10.1128/jcm.00738-15
|View full text |Cite
|
Sign up to set email alerts
|

Clonogrouping, a Rapid Multiplex PCR Method for Identification of Major Clones of Listeria monocytogenes

Abstract: f Three multiplex PCR assays were developed to identify the 11 most common Listeria monocytogenes clones in clinical and food samples; 270 (95.7%) of 282 strains of serogroups IVb, IIb, IIa, and IIc were identified accurately. This novel tool is a rapid and efficient alternative to multilocus sequence typing for identification of L. monocytogenes clones. Human and food isolates of the food-borne pathogen Listeria monocytogenes belong predominantly to two phylogenetic lineages (1-3). Lineage I isolates belong m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…The absence of LIPI3 in two samples of lineage II was expected as the sequence types have been reported to lack it LIPI [1]. The LIPI4 is a newly described Listeria pathogenicity island [56] which encodes for the genes that annotated as a cellobiose family PTS system [55], and it was not identified in any of the strains identified in this study. The LIPI4 appears to be strongly associated with ST4 isolates [1]; hence, it was not observed in the current study.…”
Section: Discussionmentioning
confidence: 56%
“…The absence of LIPI3 in two samples of lineage II was expected as the sequence types have been reported to lack it LIPI [1]. The LIPI4 is a newly described Listeria pathogenicity island [56] which encodes for the genes that annotated as a cellobiose family PTS system [55], and it was not identified in any of the strains identified in this study. The LIPI4 appears to be strongly associated with ST4 isolates [1]; hence, it was not observed in the current study.…”
Section: Discussionmentioning
confidence: 56%
“…in raw fish and shrimp samples, recently reviewed in Jami, Ghanbari, Zunabovic, Domig, and Kneifel (2014). In these reports, the rate of L. monocytogenes contamination in raw fish and shrimp samples ranged from 43.3% (Chen et al, 2010) to 0% (Kuzmanovi c et al, 2011;Minami et al, 2010;Wang, Chern, Li, Yan, & Hsieh, 2012).…”
Section: Resultsmentioning
confidence: 95%
“…Many studies have reported the incidence of L. monocytogenes in fruits and vegetables (Hadjilouka, Andritsos, Paramithiotis, Mataragas, & Drosinos, 2014;Montero et al, 2015), dairy products (Dalzini et al, 2015;Karthikeyan, Gunasekaran, & Rajendhran, 2015;Soni, Singh, Singh, & Dubey, 2013), meat (Hadjilouka et al, 2014;Kovacevic, Mesak, & Allen, 2012;Montero et al, 2015), fish (Chou & Wang, 2006;Kovacevic et al, 2012;Wang et al, 2013), seafood products (Boerlin, Boerlin-Petzold, Bannerman, Bille, & Jemmi, 1997;Li et al, 2015;Miya, Takahashi, Ishikawa, Fujii, & Kimura, 2010;Momtaz & Yadollahi, 2013), and food processing environments (Chen, Pyla, Kim, Silva, & Jung, 2010;Li et al, 2015). However, the occurrence of L. monocytogenes in seafood has received less attention in Iran and very limited information is available on the prevalence and contamination levels of Listeria spp.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A validation set of 386 Listeria strains representative of Listeria genus and L. monocytogenes diversity (Chenal-Francisque et al, 2015) was first analyzed (Table 1). A particular focus was given to L. monocytogenes (n=353), to fully cover the diversity of this species, which is the main common pathogenic Listeria isolated in clinical and food microbiological laboratories and responsible for human listeriosis.…”
mentioning
confidence: 99%